2010
DOI: 10.1007/978-3-642-14075-4_18
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Experiment Combining Virtual Reality Haptic Shoes and Audio Synthesis

Abstract: Abstract. We describe a system that can provide combined auditory and haptic sensations that arise while walking on different grounds. The simulation is based on a physical model that drives both haptic transducers embedded in sandals and headphones. The model is able to represent walking interactions with solid surfaces that can creak, be covered with crumpling material. The simulation responds to pressure on the floor by a vibrotactile signal felt by the feet. In a preliminary discrimination experiment, 15 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…These interactions may include impacts, friction or fractures events. Turchet et al presented such an approach based on Hunt-Crossley interaction [4] in conjunction with a pair of augmented sandals, and demonstrated that users are able to recognize most of the simulated material types [17]. Another physical model approach uses acceleration data, measured during walking on fragile structures such as aluminum foil and paper, to design a spectrum-based synthesis model [18].…”
Section: ) Materials Synthesis Approachmentioning
confidence: 99%
“…These interactions may include impacts, friction or fractures events. Turchet et al presented such an approach based on Hunt-Crossley interaction [4] in conjunction with a pair of augmented sandals, and demonstrated that users are able to recognize most of the simulated material types [17]. Another physical model approach uses acceleration data, measured during walking on fragile structures such as aluminum foil and paper, to design a spectrum-based synthesis model [18].…”
Section: ) Materials Synthesis Approachmentioning
confidence: 99%
“…The signals are displayed through custom shoes equipped with loudspeakers and haptic actuators. Nordahl et al [5] developed a similar approach with rigid, friction and aggregate models. They conducted a material recognition experiment, showing that some material properties could be conveyed through haptic rendering alone.…”
Section: Related Workmentioning
confidence: 99%
“…In this context, several researchers have recently demonstrated encouraging results by modeling and rendering different materials through highfrequency vibrations. For example, several solid materials can be perceived through measurement-based approaches [1]- [4], while physically based approaches have been used for simulating both solids such as wood and metal [5] and aggregates such as gravel and snow [6]. Display can be achieved by the wide availability of offthe-shelf and easily built vibrotactile hardware (actuated floors [7], shoes [8], and hand-held transducers [9]) supporting bodily interaction with virtual materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The company Nike has also developed an accelerometer which can be attached to running shoes and connected to an iPod, in such a way that, when a person runs, the iPod tracks and reports different information. Shoes enhanced with sensors and actuators were presented in [6], and an experiment was run in order to evaluate ability of subjects to recognize the virtual simulated surfaces driven by such shoes. Results showed that subjects were able to recognize simulated surfaces when rendered both using auditory and haptic at feet level.…”
Section: Previous Workmentioning
confidence: 99%